Răspunsuri

Cel mai inteligent răspuns!
2014-04-21T12:24:13+03:00
A) f(1)=3 ⇒ A∉graficului funcției
  f(-1)=-1 ⇒ B∈graficului funcției
b) 
2-f(x+1)=3f(x) \\ 2-[2(x+1)+1]=3(2x+1) \\ 2-2(x+1)-1=6x+3 \\ 2-2x-3=6x+3 \\ 8x=-4 \\ x=- \frac{4}{8}=- \frac{1}{2}
1 5 1
2014-04-21T12:30:50+03:00
A) f(1)=2*1+1=3, adica A(1,4) nu apartine graficului
f(-1)=(-1)*2+1=-2+1=-1, adica B(-1,-1) apartine graficului
b) 2-2(x+1)-1=3(2x+1)
   2-2x-2-1=6x+1
 -2=8x
   x=-2/8
   x=-1/4
   x=-0,25









b)2-2(x+1)-1=3
b)2-2(x+1)-1=3(2x+1);-2x-1=6x+3;-8x=4;x=-4/8;x=-0.5